A Little of Everything, Just In Time: Multimodal Opioid-Sparing Anesthesia for a Twin Pregnancy in Decompensated Heart Failure Caused by Severe Mitral Stenosis - Muhammad Imam Mulia Muhammad Imam; Arief Cahyadi Arief (Frontiers on Healthcare Research, 2026)
Background: Rheumatic heart disease remains a leading cause of valvular heart disease among women of reproductive age in low- and middle-income countries. Severe mitral stenosis complicating pregnancy substantially increases the risk of acute cardiac decompensation because of the hemodynamic load imposed by gestation, and anesthetic management becomes considerably more complex when it is combined with atrial fibrillation with a rapid ventricular response and a multifetal pregnancy. Reports describing general anesthesia for cesarean delivery in a twin pregnancy complicated by both severe mitral stenosis and atrial fibrillation remain scarce, which limits the guidance available to clinicians who face this specific combination. Case Presentation: A 43-year-old woman, gravida 5 para 4 abortus 0, with a twin pregnancy at 32 weeks’ gestation was referred for emergency cesarean delivery because of acute decompensated heart failure secondary to rheumatic heart disease, with atrial fibrillation with a rapid ventricular response (AF-RVR) and severe mitral stenosis. Severe dyspnea that improved only marginally with upright positioning, together with an ongoing therapeutic heparin infusion, precluded neuraxial anesthesia. General anesthesia was therefore planned using a modified, opioid-sparing induction that combined low-dose propofol, ketamine, and dexmedetomidine under invasive hemodynamic monitoring. Two live infants were delivered; postpartum ventricular rate control was achieved with intravenous digoxin followed by amiodarone, alongside vasopressor and diuretic support. The patient was extubated on postoperative day 1 without further cardiopulmonary complications. Discussion: The anesthetic strategy in mitral stenosis with AF-RVR must be directed toward avoiding tachycardia, preserving preload, and maintaining hemodynamic stability. These goals are difficult to reconcile with the sympathetic blockade produced by neuraxial techniques when these are otherwise contraindicated. A multimodal, opioid-sparing approach that layered dexmedetomidine and ketamine preserved maternal hemodynamics and respiratory drive while limiting opioid exposure before delivery to a single low dose of fentanyl given at induction; definitive antiarrhythmic therapy was deferred until after both infants had been born. Conclusion: General anesthesia with a multimodal opioid-sparing strategy is a feasible and effective approach for high-risk parturients with stenotic valvular disease and arrhythmia when neuraxial techniques are contraindicated, provided that care is delivered through close multidisciplinary collaboration. The principal lesson is that sequencing several low-dose non-opioid agents, rather than avoiding opioids altogether, can preserve both maternal hemodynamic stability and fetal well-being in this setting.